DEVELOPING PROFESSIONAL COMMUNICATIVE COMPETENCE IN TECHNICAL UNIVERSITY STUDENTS THROUGH DIFFERENTIATED VOCABULARY INSTRUCTION - Turdalieva Umida (International Journal of Literature and Language Studies, 2026)
ABSTRACT. This article investigates the role of differentiated vocabulary instruction in developing professional communicative competence among technical university students. The study analyses vocabulary teaching strategies designed according to the principles of differentiated instruction and examines their impact on students’ professional communication skills. The findings demonstrate that differentiated vocabulary instruction significantly expands students’ technical lexical repertoire, strengthens their professional written and oral communication abilities, and enhances their engagement in the learning process. Practical recommendations for ESP instructors are also presented.